Reinterpreting Ihdad in The Context Of Modernity: An Analysis From The Shafi’i School of Thought on The Practices of The Village Community of Pengambengan, Bali - Dwi Juniarty, Mila; Hasani; Muslihun; Wahyudi (Institut Agama Islam Yasni Bungo, 2026)
This study aims to analyze the application of iḥdād for women during the ‘iddah period following a spouse’s death in the modern era, as well as to examine its alignment with the Shafi’i school of thought in Pengambengan Village, Negara Subdistrict, Jembrana Regency, Bali. This study employs a qualitative method with a case study approach to gain a deep understanding of the social practices developing within the community. Data were collected through in-depth interviews with informants, direct observation of social conditions, and a documentary study of Islamic legal sources within the Shafi’i School. Data analysis was conducted using an interactive model encompassing data reduction, data presentation, and the systematic drawing of conclusions. The results of the study indicate that the majority of women in Pengambengan Village still observe iḥdād in accordance with the provisions of Shafi’i fiqh, particularly regarding the prohibition on adornment, the use of perfumes, and restrictions on activities outside the home during the ‘iddah period. However, in practice, there are several forms of adaptation influenced by economic demands and social realities, such as the need to work or meet daily living needs. These adjustments are made within limited parameters and continue to consider the principle of public interest, without substantially contradicting the fundamental provisions of the Shafi’i School. Thus, it can be concluded that the application of iḥdād in the modern era is not entirely rigid but rather adaptive and contextual, without undermining the normative values that form the primary foundation of Islamic law.